2020
DOI: 10.1177/0379572120945904
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Physical, Economic, and Policy Components of the Food Environment to Create Sustainable Healthy Diets

Abstract: Background: Sustainable healthy diets are those dietary patterns that promote all dimensions of individuals’ health and well-being; have low environmental pressure and impact; are accessible, affordable, safe, and equitable; and are culturally acceptable. The food environment, defined as the interface between the wider food system and consumer’s food acquisition and consumption, is critical for ensuring equitable access to foods that are healthy, safe, affordable, and appealing. Discussion: Current food enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 90 publications
0
29
1
Order By: Relevance
“…While we did not find any other studies reporting associations between the availability of markets and the nutritional quality of food purchases, we did find studies reporting positive associations between access to mobile food markets and FV intake [ 47 , 48 ]. However, our findings showed that having multiple markets around the home was associated with lower nutritional quality of monthly food purchases.…”
Section: Discussioncontrasting
confidence: 81%
“…While we did not find any other studies reporting associations between the availability of markets and the nutritional quality of food purchases, we did find studies reporting positive associations between access to mobile food markets and FV intake [ 47 , 48 ]. However, our findings showed that having multiple markets around the home was associated with lower nutritional quality of monthly food purchases.…”
Section: Discussioncontrasting
confidence: 81%
“…In recent years, as the threat of climate change on food production and planetary health has gained attention, the topic of healthy and sustainable diets has created momentum amongst researchers and agencies of the United Nations. There has also been a shift in focus away from working with individuals on their dietary decision‐making processes, towards efforts which create a food system that enables healthier food options and eating patterns as the default 44 . There is an increased appreciation of Indigenous peoples' food systems and knowledge required to maintain a balance between human–ecological interactions 24 .…”
Section: Resultsmentioning
confidence: 99%
“… Local government‐led strategies as part of the Milan Urban Food Policy Pact (International) 113,114 Food system sustainability from local to global approach (International) 115 Participatory food policy‐making process – Australian case study (Australia) 116 Shaping physical, economic and policy components of food environments for healthy and sustainable diets (International) 44 Benchmarking as a public health strategy to create healthy food environments – evaluation of INFORMAS (International) 117 Improving food environments using INFORMAS (New Zealand) 118 Multi‐sector participatory approach working with community stores to enhance food security in remote Indigenous communities (Australia) 119 Including alternative food networks (e.g. non‐supermarket retail options and civil society groups) in urban policy (Italy) 120 …”
Section: Resultsmentioning
confidence: 99%
“…“Current food environments are creating inequities, and sustainable healthy foods are generally more accessible for those of higher socioeconomic status” [ 83 ]. Some studies from Hungary also concluded that healthy food choice depends on the education level of people and also the financial situation [ 45 , 84 ].…”
Section: Resultsmentioning
confidence: 99%